Port-related conflict at port of Gothenburg: Consequences from a fashion retailer's perspective - Erica Lindroth; Hà Huong; Rickard Bergqvist (Journal of Shipping and Trade (JST), 2020)
Previous research have distinguished the risks of supply chain disruptions and the negative effect of supply chain disruption on operational performance in terms of sales, costs and inventory. However, few researchers have studied supply chain risk management and strategies in relation to port conflicts. The 2016 port conflict at a major logistics port in Scandinavia, the Port of Gothenburg, posed an opportunity to study risk management and strategies in the context of major port disruptions, in this case, a labour conflict. The fashion retail industry was affected especially hard due to the short product life cycles and this paper, by means of case study method and analysis, investigates five cases in order to understand how they were affected and what mitigation strategies was used. Results illustrates that during the port conflict, the percentage of increase in logistics cost ranged between 15% and 70%, greatly affected by what mitigation strategy was used by the case company.
Keywords: 650; Port conflicts; Risk management; Fashion industry; Supply chain disruption